KESALAHAN GRAMATIKA BAHASA INGGRIS DALAM MENULIS TEKS DESKRIPTIF OLEH MAHASISWA FARMASI SEMESTER DUA UNIVERSITAS SARI MUTIARA INDONESIA - Arman Bemby Sinaga; F Ari Anggraini Sebayang; Ordekoria Saragih (Jurnal Mutiara Pendidikan Indonesia, 2021)
This research title is Grammatical Errors in Writing Descriptive Text by Second Semester of Pharmacy Students of Sari Mutiara Indonesia University. This Research was conducted to find out the kinds of grammatical errors in writing descriptive text by second semester of Parmacy students of Sari Mutiara Indonesia University and to find out the dominant error. This research was conducted through descriptive qualitative by documentary research. This research was conducted to the pharmacy students of Sari Mutiara Indonesia University through survey and documentary research. This research found that errors in producing verb group (130), subject verb agreement (57), preposition (19), articles (13), plural (11), pronoun (27), conjunction (8). It was concluded that the dominant error was in producing verb group.